THE ASSESSMENT OF PRETEST PROBABILITY IN OBSTRUCTIVE CORONARY LESION DIAGNOSTICS: UNRESOLVED ISSUES - A. N. Sumin (Российский кардиологический журнал, 2017)
Invasive coronary arteriography is a gold standard in CHD diagnostics, however in many cases it ends with none significant obstructive lesions revealed. Recently, an algorithm was implemented, based on the assessment of pretest probability (PTP) of coronary heart disease. It is noteworthy that current international guidelines do differently recommend the PTP calculation, there are differences in further tactics of non-invasive and invasive investigation. Also, real clinical practice witness on significant overestimation of PTP when the recommended scores are in use. The review is focused on different PTP scores, the reasons discussed for differences in results of application. This helps to make clinical usage more conscious.